Not Just About Salary: An Analysis of the Role of Organizational Culture on Employee Engagement - Manalu, Della Edelweiss; Sibatuara, Rahel Gabriel Rosabeth; Meyvanali (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study aims to examine how Organizational Culture influences Employee Engagement. By conducting a comprehensive literature review, the research adopts an Organizational Culture perspective to explore the link between these two variables. The findings from the systematic literature review indicate that Organizational Culture plays a significant role in determining the level of Employee Engagement. However, the study also reveals a need for further research to pinpoint specific elements of Organizational Culture that can effectively enhance Employee Engagement, given the wide variety of Organizational Cultures. Future research could focus on developing more precise tools to measure relevant dimensions of Organizational Culture in relation to Employee Engagement and testing more sophisticated theoretical models to explain their connection.